Native title : a five year retrospective 1994-1998 : report on the operations of the Native Title Act 1993 and the effectiveness of the National Native Title Tribunal /|National Native Title Tribunal. - National Native Title Tribunal (Australia) (Perth, W.A. : National Native Title Tribunal, 1999)
Reports on the operations of the National Native Title Tribunal from the commencement of the Native Title Act until the commencement of the 1998 amendments; role of the Tribunal as mediator; number of agreements mediated; future act regime; appendices include international experience, Tribunal timeline, list of Tribunal seminars, products and publications, future act workload summary, agreements summary, number of applications lodged 1994-1998.
"February 1999"
Includes bibliographical references (p. 93-111).
Keywords: Australia; National Native Title Tribunal (Australia); Native title (Australia) -- History; Native title - National Native Title Tribunal; Native title - Law and legislation - Commonwealth; Native title - Agreements; Native title - National Native Title Tribunal - Mediation; Native title - Future acts; Australia